The Bear Grylls Adventure. Book 11, The Arctic Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2019)
The eleventh in the fun 12-book collectible series for young readers from survival expert and Chief Scout BEAR GRYLLS. Joe gets on well with everyone, enjoys camp and all the activities and is always up for a challenge.